МЕТОДИЧЕСКИЕ ОСОБЕННОСТИ И ХАРАКТЕР ФОРМИРОВАНИЯ ПОНЯТИЙ ПО ХИМИИ - Бектурганова, З.К.; Жумамуратов, Р. (SCIENCE and SOCIETY, 2016)
The article deals with the formation of organic chemistry concepts, principles of its gradual development, such as chemical structure, electronic and dimensional structure.
Keywords: logical operations; concrete and abstract correlation; formation; content; cognitive meaning